Capacity of normal and turbo-roundabouts: comparative analysis - Vasconcelos, Luís (2012)
While researchers agree as to the safety benefits of turbo roundabouts, their improvements in terms of capacity and delay remain open to discussion. This is mostly because previous research is based on capacity models that do not fully describe the complex interactions between the traffic streams on multilane roundabouts. This paper proposes a procedure to calculate capacity based on gap-acceptance theory. It addresses the limitations mentioned by accounting for usually disregarded effects such as the dynamic choice of the entry lane and unequal allocation of traffic in the circulatory lanes. Capacities were calculated for a wide range of demand scenarios and it has been shown that only under demand scenarios that are very specific and uncommon in real world networks, associated with very high percentages of rightturning entry traffic, can a standard turbo roundabout be expected to provide more capacity than the equivalent two-lane roundabout. It has also been shown that two lane roundabouts can normally be expected to provide capacities 20 to 30% above those of comparable turbo roundabouts.